POTENTIAL UTILIZATION OF FLY ASH AND BOTTOM ASH WASTES FOR NATIONAL CAPITAL INTEGRATED COASTAL DEVELOPMENT - Fuzi Suciati; Dwindrata Aviantara (Badan Pengkajian dan Penerapan Teknologi (BPPT), 2022)
Jakarta's coastal areas are prone to flooding problems. Floods are generally caused by high-intensity rain, river runoff and tidal waves from sea water. The main causes of this situation are land subsidence, increased river discharge from upstream areas and local rainfall which is not accommodated by the existing drainage system. With the plan to build a giant sea wall in the bay of Jakarta, it is estimated that the sea water rob that hit DKI Jakarta can be overcome. The construction of the giant sea wall and PTPIN requires massive materials for concrete and civil constructions. Fly ash and bottom ash wastes from coal fired power plant have physical characteristics that are estimated to meet PTPIN's needs. In addition, the characteristics of TCLP, LD50 and radioactive of FABA wastes also meet the PP22/2021 criteria. By utilizing the FABA wastes, the exploitation of natural materials for the construction of PTPIN can be avoided so that the PTPIN development process takes place in an environmentally friendly and sustainable manner. Utilization of FABA wastes is in line with circular economy efforts and can change the mindset of FABA wastes from a cost center to a revenue center.